Роль маркетингових інтернет-комунікацій при реінжинірингу бізнес-процесів суб’єктів туристичної діяльності - Іванюк, У. В.; Ярмола, К. М.; Ivaniuk, U.; Yarmola, K. M. (Видавництво Львівської політехніки, 2024)
У статті досліджено маркетингові інтернет-комунікації під час проведення реінжинірингу бізнес-процесів суб’єктів туристичної діяльності. В контексті активної цифрової трансформації економіки та суспільства використання маркетингових інтернет-комунікацій стає ключовим чинником оптимізації та підвищення ефективності бізнес-процесів туристичних підприємств. Проаналізовано роль соціальних медіа, вебсайтів, блогів та інших інтернет-платформ у поліпшенні якості та підвищенні ефективності процесів реінжинірингу. Розглянуто та доповнено систему факторів, які впливають на результат реінжинірингу бізнес-процесів. Відзначено важливість додаткової уваги до інформаційних комунікаційних стратегій у контексті туристичної галузі та запропоновано рекомендації щодо оптимального використання інтернет-комунікаційних інструментів для досягнення успішних результатів у реінжинірингу бізнес-процесів.

Purpose. Research and analyze the significance of marketing internet communications in reengineering business processes within the tourism activities sector. Design/methodology/approach. The following methods were used in research: theoretical generalization (to determine the essence of business processes reengineering of tourism activity subjects), grouping (to identify and generalize the factors that influence business processes reengineering), analysis and synthesis (to determine the features of business processes reengineering in tourism business), system approach (to substant the elements and means of digital communications development of tourism activity subjects). The visibility of the presented results is ensured by the data graphical presentation, the methods of logical generalization and systematic approach were used to form the conclusions. Findings. Reengineering has become a high-quality tool for finding and implementing ways to improve the efficiency of the enterprises and organizations functioning, as it involves the identification of problem areas and the justification of prospective solutions with the highest level of detail. The application of marketing aspects and the development of internet communications system can be particularly promising vector for the business processes reengineering of tourist enterprises. It is important during reengineering, enterprises should make changes not only in problem areas, but also in other areas (marketing, information, etc.), because reengineering covers all spheres of the organization's activity. Nowadays traditional marketing tools are being replaced by digital that use the capabilities of Internet technologies. In recent decades, information technologies have been actively integrated into all spheres of enterprise activity, marketing was no exception. Business processes reengineering should be supported by marketing, information and strategic measures that will enhance the effect of its implementation. Practical implications. The practical significance of the obtained research results lies in the business processes digitalization of tourist enterprises, which will contribute to the growth of their economic and managerial efficiency. Originality/value. The scientific novelty of the research results lies in the study of factors that affect the result of business process reengineering and added to them two new factors (marketing and informational). An analysis of the social media usage by Ukrainian tourism enterprises in their activities was also carried out. Potential mechanisms for using price policy as a lever for targeted demand management in the Internet environment were proposed.
The role of marketing internet communications in the re-engineering of business processes of tourist activities
Keywords: суб’єкти туристичної діяльності; бізнес-процес; реінжиніринг бізнес-процесів; маркетингова діяльність; інтернет-комуніка; tourism activity subjects; business process; business process reengineering; marketing activity; internet communication; social media; L15; L86; М10; M39; 005.591.4; 338.48